2012
DOI: 10.4103/0972-2327.95003
|View full text |Cite
|
Sign up to set email alerts
|

Jervell and Lange-Nielson Syndrome masquerading as intractable epilepsy

Abstract: The long QT syndrome (LQTS) is a cause of syncope and sudden death. Jervell and Lange–Nielson syndrome (JLNS) is an uncommon form of LQTS, having autosomal recessive transmission, and is associated with congenital deafness. We report a case of JLNS in a child who presented to us with refractory epilepsy. The cardiac cause of seizures was suspected as the child was hypotensive and pulseless during the episode of seizures. The child was diagnosed as JLNS based on Schwartz diagnostic criteria for LQTS and congeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Patients with SADS can present with or be (incorrectly) labelled as having epilepsy. [22][23][24][25] Guidelines on post-mortem examination of SUD in the young have been published by the Royal College of Pathologists of Australasia (https://www.rcpa. edu.au/getattachment/89884c69-f066-411d-a3d1-39460444db13/Guidelines-on-Autopsy-Practice.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SADS can present with or be (incorrectly) labelled as having epilepsy. [22][23][24][25] Guidelines on post-mortem examination of SUD in the young have been published by the Royal College of Pathologists of Australasia (https://www.rcpa. edu.au/getattachment/89884c69-f066-411d-a3d1-39460444db13/Guidelines-on-Autopsy-Practice.…”
Section: Discussionmentioning
confidence: 99%
“…Qureshi et al [] reported compound heterozygous mutations in a consanguineous Indian family with JLNS. Reports of other Indian patients with JLNS also note consanguinity in all; though molecular studies were not performed [Sundar et al, ; Sathyamurthy et al, ; Goyal et al, ]. Patients of Indian ethnicity with AR RWS have not been described till date.…”
Section: Discussionmentioning
confidence: 99%
“… 27. , 28. ] A concerted effort across the nation to gather existing data, plug the gaps in clinical evaluation and proceed with genetic counseling and testing is the way forward in this era where research-based as well as commercial genotyping opportunities with sound bioinformatics backing are currently more readily available.…”
Section: Diagnostic Evolutionmentioning
confidence: 99%